Board meeting, promoter CEO and firm performance: Evidence from India - Minati Sahoo; Kailash B. L. Srivastava; Neeraj Gupta; Sachin Kumar Mittal; Priti Bakhshi; Tarun Agarwal (Cogent Economics & Finance, 2023)
The study examined the relationship between board characteristics and firm performance and the moderating effects of firm size, the board size, and firm age between board characteristics and firm performance. This study considers the legal reforms implemented after the Indian Companies Act 2013. Data from 113 firms with 904 observations from 2012-13 to 2019-20 were analyzed using the fixed panel data estimation approach. A subsample analysis is employed, dividing the data by firm size, the board size, and firm age to test the robustness of the results. The results show that the board size, female director, Promoter CEOs, meeting frequencies, and attendance rate positively affect firm performance. At the same time, the impact of the independent directors and busy CEO has a negative impact on performance. Male CEOs are beneficial for firm performance. The study adds to the literature by identifying critical board characteristics in light of ongoing regulatory reform in emerging economies like India. It has implications for regulators and policymakers who are entrusted with the framing of corporate governance policies.
Keywords: 330; Board meeting; clause 49; corporate governance; firm performance; promoter CEO